The Effectiveness of Criminal Sanctions in Preventing Corruption: A Literature Review of the Indonesian Legal System - Suhartono, Suhartono; Sudjai, Sudjai; Darmawan, Didit; Rizky, Muchamad Catur; Saktiawan, Pratolo (Bulletin of Science, Technology and Society, 2024)
This research aims to analyze the effectiveness of the application of criminal sanctions in preventing corruption in Indonesia, with a legal literature-based approach. Through a normative juridical study, this research explores how the application of criminal sanctions, both repressive and preventive, can affect the incidence of corruption. This research also explores the legal reform efforts needed to create a more effective law enforcement system. The results show that the main obstacles to the effectiveness of criminal sanctions are weak supervision and inconsistency in the application of the law, which has implications for the low deterrent effect. The study also reveals the importance of synergy between strict criminal threats and prevention strategies based on anti-corruption education values to build a strong legal culture. From a comparative law perspective, the study suggests the adoption of best practices from other countries, such as Singapore and Norway, to strengthen corruption eradication efforts. Thus, this study provides important insights for policy makers and law enforcers to optimize the function of criminal sanctions as an effective prevention tool.